2008
DOI: 10.1007/s11205-008-9349-x
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Life in Hong Kong

Abstract: Hong Kong, Quality of life, Democracy, Asia, AsiaBarometer, Happiness,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…Table 1 presents the profile of respondents that were surveyed in the 2006 AsiaBarometer study. The respondents in the AsiaBarometer survey were reported to be fairly representative of the respective national populations (see Shu and Zhu 2009;Inoguchi and Shin 2009;Park 2009;Sing 2009;Tambyah et al 2009). …”
Section: The Asiabarometer Surveymentioning
confidence: 99%
“…Table 1 presents the profile of respondents that were surveyed in the 2006 AsiaBarometer study. The respondents in the AsiaBarometer survey were reported to be fairly representative of the respective national populations (see Shu and Zhu 2009;Inoguchi and Shin 2009;Park 2009;Sing 2009;Tambyah et al 2009). …”
Section: The Asiabarometer Surveymentioning
confidence: 99%
“…Prior research has indicated that there are considerable barriers against undertaking voluntary work in Hong Kong. Although Hong Kong citizens believe that firms should contribute to the community (Ramasamy and Yeung 2009), typically they are not proactive in this process (Sing 2009). Very few Hong Kong residents regard contributing to the community as an important life attribute (Sing 2009).…”
Section: Research Objectivesmentioning
confidence: 99%
“…Although Hong Kong citizens believe that firms should contribute to the community (Ramasamy and Yeung 2009), typically they are not proactive in this process (Sing 2009). Very few Hong Kong residents regard contributing to the community as an important life attribute (Sing 2009). There is no established tradition of helping the poor, vulnerable and needy in society (Wong 2008, p. 332) and materialistic values predominate (Wong and Wan 2009).…”
Section: Research Objectivesmentioning
confidence: 99%
“…Economically, Hong Kong is considered as a service economy with low taxation, labour freedom, efficient regulatory frameworks and free trade, ranked freest in the world by the Index for Economic Freedom, despite recent concerns about higher levels of perceived corruption and undermined public trust (The Heritage Foundation, 2015). As such, the population is described by Sing (2009) as characterised by a deep desire for materialistic attainment; however, the income gap is the highest in the AsiaPacific with a Gini coefficient of 53.7 measured on gross income, and 47.5 post-tax and post social transfers (Hong Kong SAR Government, 2011).…”
Section: History and Societymentioning
confidence: 99%